2020
DOI: 10.1177/1069072720918195
|View full text |Cite
|
Sign up to set email alerts
|

The Only Constant Is Change? Movement Capital and Perceived Employability

Abstract: This study examines to what extent the four aspects of movement capital (i.e., human capital, adaptability, self-awareness, and social capital) contribute to individuals’ perceived employability. Building on the model of career mobility, we expected positive effects of all movement capital aspects on perceived employability over time. Hypotheses were tested by means of longitudinal structural equation models in two samples of Belgian respondents from the private ( N = 409, 6 months between measurements) and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 51 publications
(106 reference statements)
1
23
0
1
Order By: Relevance
“…For instance, interventions could focus on the various costs of turnover such as movement capital (Peeters et al, 2020), adaptation (Brown et al, 2012;Johnston, 2018), and reinvention of work identity (Ibarra and Petriglieri, 2010) and integrate the findings from this study to illustrate the process from shock to shift. To illustrate, with the use of the findings from this study illustrations and stimuli could be developed, that elucidate the nature of shocks and the options for agentic responses.…”
Section: Limitations Theoretical and Practical Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, interventions could focus on the various costs of turnover such as movement capital (Peeters et al, 2020), adaptation (Brown et al, 2012;Johnston, 2018), and reinvention of work identity (Ibarra and Petriglieri, 2010) and integrate the findings from this study to illustrate the process from shock to shift. To illustrate, with the use of the findings from this study illustrations and stimuli could be developed, that elucidate the nature of shocks and the options for agentic responses.…”
Section: Limitations Theoretical and Practical Implicationsmentioning
confidence: 99%
“…Accordingly, career change literature captures the internal challenges and strategies to deal with career changes. Career changes entail monetary and psychological costs (e.g., Holtom et al, 2005), movement capital (Peeters et al, 2020), a large degree of adaptation (Brown et al, 2012;Johnston, 2018), and reinvention of work identity (Ibarra and Petriglieri, 2010).…”
Section: Career Changementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding antecedents of perceived employability, previous studies have found that movement capital (Forrier et al, 2015), mobility supporting activities (Veld et al, 2015), career insight (De Vos & Soens, 2008), career resilience (Peeters et al, 2020), and extrinsic job opportunities (Van Emmerik et al, 2012), promoted perceived employability. It should be noted that proactive career behaviors (Chughtai, 2019) and proactive orientation (Creed et al, 2017) had positive impacts on perceived employability.…”
Section: Literature Review and Theoretical Backgroundmentioning
confidence: 99%
“…Pitan and Muller (2019), reported that realization of labor market situation helps in enhancing student employability. As per Peeters et al, (2020), employees who are aware of labor market opportunities, tends to have high perceived employability.…”
Section: External Factorsmentioning
confidence: 99%